L’analyse multimodale de la publicité Saint Maclou – J’ai vu un tuto - Siti Mutmainatus Zahro; Diah Vitri Widayanti (Universitas Negeri Semarang, 2024)
Multimodal is a theory of communication and social semiotics. It allows us to analyze the message through linguistic and visual components. These are used to promote products to the public, called advertisements. The ad “Saint Maclou - J’ai vu un tuto” is a television advertisement combining interactions between spoken, written, and visual language. Therefore, this research has a complex meaning of linguistic and visual components so that it can be analyzed using multimodal. The Multimodal theory discussed in this research uses meta function by Halliday's theory of interpersonal meaning and the generic structure theory by Cheong. Based on the analysis, the results show that there are 15 sentences, which is a statement. The statement has an important role in providing linguistic information about the advertisement so that the message can be conveyed correctly; the generic structure consists of Lead, Display, Emblem (linguistic), Announcement, Emblem (nonlinguistic), Enhancer, and Call & Visit Information. There is an interaction between visual and linguistic components, and they complement each other, the application of learning this advertisement can be done by adjusting from level A1 to level C1 with different communicative objectives.